Exploring Academic Procrastination in Thesis Writing of English Education Students - Furqoni, Inayah; Muhayyang, Maemuna; Muhalim, Muhalim (State University of Makassar, 2025)
This research aims to explain the academic procrastination in thesis writing of English Education students. It purposed to determine (1) the tendency of academic procrastination in English Education students (2) find out the causing factors of academic procrastination in thesis writing of English Education Students. The method used in this research is the qualitative descriptive method. The participants of this research were 4 final year students of English Education Universitas Negeri Makassar. In collecting data, structured interviews are conducted by utilizing pre-provided interview questions. The results of the research concluded that (1) there is a tendency to do academic procrastination in students which is characterized by delay in starting and completing thesis, delay (lateness) in doing thesis, time gaps between plans and actual performance, and do more enjoyable activities (2) the causing factors of academic procrastination in writing thesis can be internal and external. Internally, it can be physical (sick and physically tired) and psychological (fear of being wrong, lacking ideas, fear of consultation, laziness and preferring enjoyable activities). From the external aspect, it can be in the form of facilities, environment, and writing thesis in English.Keywords: Academic Procrastination, English Education Students, Thesis Writing